Revisiting Deterrence Theory in Revisiting Deterrence Theory in the Context of Globalization: An Analysis of «Crime Substitution» as a Starting Point (International relations and international law Journal, 2025)
Deterrence theory plays an important role in controlling crime and is one of the ideological foundations of the criminal justice system. Globalization has had a significant impact on traditional crimes and crime methods, and crime substitution among countries has gradually become a norm phenomenon. Whether in the dimension of crime cost calculation, the dimension of sanction method, or the dimension of individual diversity consideration, deterrence theory has varying degrees of deficiencies and cannot effectively combat the problem of crime substitution among countries. The purpose of deterrence is to reduce the absolute number of crimes, rather than to transfer the crimes to other countries or regions. Therefore, the deterrence theory should be revised to respond to the need to reduce crime in the era of globalization. First, we should rationally recognize that crime substitution is a costly process; second, we should introduce criminological research methods into deterrence theory and focus on individual differences; finally, we should rationally recognize the deterrent effect of non-legal sanctions on potential criminals.Deterrence theory must evolve to address the complexities of crime in the globalized era. Rather than merely transferring crime across borders, deterrence theory should focus on reducing crime globally, including emerging threats such as terrorism and cybercrime. These developments call for innovations in deterrence theory to effectively prevent crime in a rapidly changing world.Key words: Crime substitution, deterrence, crime costs, non-legal factors, morality